Business process management workshops : BPM 2016 International Workshops, Rio de Janeiro, Brazil, September 19, 2016, Revised papers /: BPM 2016 International Workshops, Rio de Janeiro, Brazil, September 19, 2016, Revised papers. (2017) - Unknown
No abstract available